Perlindungan Hukum terhadap Konsumen Tabung Oksigen Hasil Modifikasi di Masa Pandemi Covid- 19 Berdasarkan Undang- Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Ni Wayan Eny Yulianti; I Nyoman Putu Budhiarta; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2022)
The circulation of modified oxygen cylinders causes the community to need legal protection for the community. So, this research aims to examine the form of legal protection for consumers who are harmed by the use of modified oxygen cylinders by business actors during the Covid-19 pandemic based on Law Number 8 of 1999 concerning Consumer Protection, and to discuss the responsibilities of business actors who harm consumers. for the circulation of modified oxygen cylinders during the Covid-19 pandemic. The normative research method uses a statutory approach, a conceptual approach, and a case approach. The legal materials of this research use primary, secondary and tertiary legal materials. Primary legal material comes from legislation relevant to the research case. Secondary legal materials consist of legal journals, law books, and the internet. And tertiary legal materials, namely supporting legal materials such as legal dictionaries, encyclopaedias and others. The technique of collecting legal materials used in this research is the technique of inventorying legislation according to the hierarchy so that it uses the library method by using the technique of recording legal materials. The results of this study can be concluded that preventive legal protection for consumers of modified oxygen cylinders with the regulation of consumer rights Article 4 UUPK and repressive protection consumers who are harmed can ask for compensation through litigation and non-litigation. Liability to consumers of modified oxygen cylinders who are harmed in the form of product responsibility based on compensation in the form of refunds or health care